Evaluation of ventilation maldistribution as an early indicator of lung disease in children with cystic fibrosis - Gustafsson, P M; Aurora, P; Lindblad, A (The European respiratory journal, 2003)
Many children with cystic fibrosis (CF), receiving modern, aggressive CF care, have normal spirometry results. This study aimed to see if homogeneity of ventilation distribution is impaired early in the course of CF lung disease, and if ventilation inhomogeneity is a more frequent finding than abnormal spirometry in children benefiting from modern CF care. The study compared spirometry findings to two indices of ventilation inhomogeneity (mixing ratio (MR) and lung clearance index (LCI)) from multiple-breath inert gas washout in 43 children with CF, aged 3-18 yrs, and 28 healthy children. In total, 10/43 CF subjects (23%) had reduced forced expiratory volume in one second (FEV1) and 14/34 (41%) showed abnormal maximum expiratory flow at 25% of forced vital capacity (MEF25). In contrast, MR was abnormal in 31/43 (72%) and LCI in 27/43 (63%). MR was abnormal in 22/33 CF subjects with normal FEV1, versus 0/28 controls (p<0.001), and abnormal MR was found in 10/20 CF subjects with normal MEF25, versus 0/22 controls (p<0.001). Nine of the 10 CF subjects with reduced FEV1 and 12/14 with abnormal MEF25 showed abnormal MR. Inert gas washout discloses airway dysfunction in the majority of children with cystic fibrosis with normal lung function judged by spirometry. These findings suggest that multiple-breath inert gas washout is of greater value than spirometry in detecting early cystic fibrosis lung disease.